Functional Sites of Ribosome Modulation Factor (RMF) Involved in the Formation of 100S Ribosome - Yoshida, Hideji; Nakayama, Hideki; Maki, Yasushi; Ueta, Masami; Wada, Chieko; Wada, Akira (Frontiers in Molecular Biosciences, 2021)
One of the important cellular events in all organisms is protein synthesis, which is catalyzed by ribosomes. The ribosomal activity is dependent on the environmental situation of the cell. Bacteria form 100S ribosomes, lacking translational activity, to survive under stress conditions such as nutrient starvation. The 100S ribosome is a dimer of two 70S ribosomes bridged through the 30S subunits. In some pathogens of gammaproteobacteria, such as Escherichia coli, Yersinia pestis, and Vibrio cholerae, the key factor for ribosomal dimerization is the small protein, ribosome modulation factor (RMF). When ribosomal dimerization by RMF is impaired, long-term bacterial survival is abolished. This shows that the interconversion system between active 70S ribosomes and inactive 100S ribosomes is an important survival strategy for bacteria. Since the induction of RMF expression inhibits bacterial growth, the data on this protein could serve as information for the development of antibiotic or bacteriostatic agents. According to the results of several structural analyses, RMF does not directly connect two ribosomes, but binds to them and changes the conformation of their 30S subunits, thus promoting ribosomal dimerization. In this study, conserved RMF amino acids among 50 bacteria were selectively altered by mutagenesis to identify residues involved in ribosome binding and dimerization, respectively. As the results, some essential amino acids of RMF for the ribosomal binding and dimerization were elucidated.